ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BRAND LOYALITY PELANGGAN TOKO ROTI TNB BAKESHOP - Rahadyan Tajuddien (Yayasan Sahabat Cendekia Jaya, 2024)
Purpose. This research aims to determine the analysis of factors that influence Customer Brand Loyalty partially and simultaneously at the TNB Bakeshop Bakery Methods. This research method uses the explanatory factor analysis method, using 102 respondents. Statistical calculations in this research used the SPSS 26.0 program and AMOS Graphics. The method used in data analysis was the Structural Equation Model (SEM). Findings. This research shows that the average social media marketing variable index of 43.25% has a positive role in brand loyalty, the product quality variable index of 43.98% has a positive role in brand loyalty and the customer satisfaction variable index of 42.45% has a positive role in brand loyalty. Implication. The variable that has a very positive influence is social media marketing and it is significant on customer satisfaction and the higher the product quality, the positive influence it will have on brand loyalty